Process Of The Teaching Speaking In Power Speaking Program At "Gama English Course" - Romadani, Putri; , Aryati Prasetyarini,S.Pd, M.Pd; , Hepy Adityarini, Ph.D (2017)
This article describes the result of a study in teaching speaking. The objectives of this study were to describe the process of teaching speaking in Power Speaking program at Gama English Course. The data were field note consisting of the teaching and the learning process in three branches of Gama English Course, interview with the owner of Gama English Course and teacher in three branches of Gama English Course, and syllabus consisting of the documents in three branches of Gama English Course. The techniques for collecting data in this study were observation, interview, and document. There were four steps in analyzing data, namely rereading, coding, tabulating, and drawing conclusion. The results of the study showed that (1) there were two learning objectives in Power Speaking program at Gama English Course, namely: to make the students feel comfortable in speaking English and to make students have attractive speaking ability; (2) the materials taught in Power Speaking program at Gama English Course were dominated by grammatical aspects. It can be seen from the materials written in syllabus which mostly explained tenses, adjective clause, gerund, infinitive, causative, preference, etc; (3) the teaching procedures in Power Speaking program at Gama English Course consisted of three stages, namely: pre-teaching (opening, and reviewing), while teaching (teaching, and practicing), and post-teaching (check students speaking ability, and closing). Key words: Teaching Speaking, learning objective, materials, teaching procedures, and quality teachers.